2020
DOI: 10.2486/indhealth.2019-0150
|View full text |Cite
|
Sign up to set email alerts
|

Support for balancing cancer treatment and work by occupational health nurses: support structures and implementation status

Abstract: This study aimed to quantitatively grasp the structure of support for balancing cancer treatment and work among occupational health nurses (OHNs) with the current implementation status. The anonymous questionnaire was designed based on the findings of our previous qualitative study and distributed to OHNs. The degrees of support implementation for workers with cancer, superiors and colleagues, and human resource managers were assessed for each item. Factor analysis of support items was conducted, and Wilcoxon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Nishikido et al reported that OHNs provided support in promoting TWBS not only to workers with illnesses but also to managers, and HR staff. [14][15][16][17][18][19][20] The fact that the intervention encouraged willingness and belief, empowering mutual respect and support suggests that the expected effect was achieved.…”
Section: Intervention Effects On Workers' Primary Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Nishikido et al reported that OHNs provided support in promoting TWBS not only to workers with illnesses but also to managers, and HR staff. [14][15][16][17][18][19][20] The fact that the intervention encouraged willingness and belief, empowering mutual respect and support suggests that the expected effect was achieved.…”
Section: Intervention Effects On Workers' Primary Outcomementioning
confidence: 99%
“…In SMEs that do not have full-time OPs, OHNs play a central role in providing support to promote health in the workplace. [18][19][20] The authors believe that it is necessary to conduct empirical research on the effectiveness of the TWBS program promoted by OHNs in SMEs, as no previous research has been conducted on this topic. The authors developed the "Recognition and Attitude Scale toward TWBS in SMEs" ("Recognition and Attitude Scale") as an evaluation index in a preliminary study.…”
Section: Introductionmentioning
confidence: 99%
“…Because there was no precedent study about the sense of difficulty among OHNs when we conducted this study, the items about sense of difficulty in the questionnaire were created by repeated discussions among the authors based on the results of our previous study using FGI with OHNs 18,19) and relevant literatures. Finally, we determined 11 items related to the sense of difficulty experienced by OHNs in providing support.…”
Section: Making the Questionnairementioning
confidence: 99%
“…In Japan, OHNs play varying roles from primary to tertiary prevention at workplaces and collaborate with occupational health physicians and other professionals 18) . Recently, the balance between cancer treatment and work has been an issue in workplaces because the number of cancer survivors in the working population has significantly increased with the progress in medical treatment 1) .…”
mentioning
confidence: 99%
See 1 more Smart Citation